Plexiform Neurofibroma of the Posterior Tibial Nerve Misdiagnosed as Proximal Tarsal Tunnel Syndrome: A Case Report - Nam, Sang Hyun; Kim, Jung Yeon; Ahn, Jaeki; Park, Yongbum (The Surgery Journal, 2018)
Plexiform neurofibromas of the foot are rare, benign tumors of the peripheral nerves. Diagnosis can be challenging if they present with symptoms mimicking other peripheral nerve pathologies. Tarsal tunnel syndrome is an entrapment syndrome of the entire tibial nerve behind the medial malleolus and under the flexor retinaculum. The clinical presentation typically includes posteromedial pain, positive Tinel's sign, and neurogenic signs, including both the sensation of numbness and the actual hypoesthesia and clawing of the toes.Here, we report the case of a 59-year-old female patient with plexiform neurofibroma with symptoms similar to those of tarsal tunnel syndrome. The plexiform neurofibroma was surgically excised and the nerve function was partially preserved.
Keywords: neurofibroma; tarsal tunnel syndrome; Tinel's sign